Kansas Soil Health Partnership - C. B. Pires; I. A. Ciampitti; D. A. Ruiz Diaz; M. V. Sarto; Charles Rice (Kansas Agricultural Experiment Station Research Reports, 2021)
This study was part of a farmer-led initiative that fosters transformation in agriculture through improved soil health, benefitting farmer profitability, supporting a stable food supply, and preserving the environment. This study’s objective was to measure the effect of soil management strategies on the soil microbial community distribution and activity. Four farmers in Kansas were accepted into the program to conduct on-farm comparisons of a standard farm practice and an improved practice. This was ongoing research, and for this field research report, we are presenting the study at one of the selected farms. This site was located near Bucyrus, Miami County (38°44’30” N, 94°42’30” W, elevation: 1109 ft), with a Grundy silt loam. The improved practice was the incorporation of cover crops into a long-term no-till corn-soybean rotation. The experimental design was four replicated strips of the farmer standard practice and the improved practice. Soil samples were taken on a GPS coordinated grid at 0 to 2 inches soil depth before implementing the cover crops (baseline), and at the third year of the study. Soil biological health indicators included soil organic matter, soil microbial biomass, total fungi, total bacteria, and β-glucosidase (βG) activity. Soil organic matter and βG activity were compared between initial and third-year. Interpolated maps evaluated the spatial distribution of the soil microbial community. Two years of cover crops increased enzyme activity. Soil microbial biomass and soil organic matter were significantly (P<0.001) correlated. Our results suggest that soil organic matter was a key driver of the spatial distribution of the soil microbial community.
Keywords: soil biology; organic matter; sustainable intensification; cover crops